Mathematical Insights into the Effects of Levodopa - Reed, Michael C.; Best, Janet A.; Nijhout, H. F. (Frontiers in Integrative Neuroscience, 2012)
Parkinson's disease has been traditionally thought of as a dopaminergic disease in which cells of the substantia nigra pars compacta (SNc) die. However, accumulating evidence implies an important role for the serotonergic system in Parkinson's disease in general and in physiological responses to levodopa therapy, the fi□rst line of treatment. We use a mathematical model to investigate the consequences of levodopa therapy on the serotonergic system and on the pulsatile release of dopamine from dopaminergic and serotonergic terminals in the striatum. Levodopa competes with tyrosine and tryptophan at the blood-brain barrier and is taken up by serotonin neurons in which it competes for aromatic amino acid decarboxylase. The dopamine produced competes with serotonin for packaging into vesicles. We study how this competition aff□ects the release of dopamine into the striatum during a levodopa dose and how the time course of extracellular dopamine changes as SNc cells die. We explain the shortening of the therapeutic time window for the effi□cacy of levodopa as Parkinson's disease progresses. Finally, we study the eff□ects 5HT1a and 5HT1b autoreceptor agonists and explain why they have a synergistic eff□ect and why they lengthen the therapeutic time window.